On product of generalized s-convex functions and new inequalities on fractal sets - Kilicman, Adem; Saleh, Wedad (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
In this article, we give some new inequalities for product of generalized s-convex functions on the co-ordinates on fractal sets. Furthermore, this article points out some of these kinds of inequalities.